Characteristics of high potential employees: employees’ perspective - Juhdi, Nurita (2013)

(untitled)
The objective of the study was to determine the major characteristics of high potential (HIPO) employees. HIPOs, as defined by Schumacher (2009), are employees who produce excellent work performance consistently. Prior research indicated various characteristics and traits portraying HIPO personalities, characters and competence but the studies only discussed the matter conceptually and in theory.Based on the data collected from 329 respondents, the overall study findings indicated that the term HIPO was made up of different competences as projected by the previous authors. It is reasonable to understand that a person with HIPO must be an individual who always want to produce results beyond expectation or at least meet with the job requirement. The findings suggest that a person with strong drive for high performance is less likely to leave, and must also have learning agility with leadership spirit. For a person with learning agility, besides having leadership spirit and drive for high performance, he/she is also highly engaged to the job and the organization. But for a person with strong leadership spirit, it is not just learning agility and drive for high performance that are important, the person also has high education level, seniority and more engaged to the organization. Nonetheless, positive relationship between leadership spirit and turnover intention will remain as a nightmare to employers. This implies that the more the person looks forward to advancement and building relationships, the more he/she intends to leave the organization.